"If the reindeer die, everything dies": The mental health of a Sámi community exposed to a mining project in Swedish Sápmi. Issue 1 (1st January 2021) - Blåhed, Hanna; San Sebastián, Miguel
ABSTRACT: In 2006, a British mining company started the process of extracting ore from Gállok/Kallak, in Swedish Sápmi. These grounds are used all year round for reindeer herding by the Sámi community Jåhkågasska tjiellde. While environmental impact assessments should be conducted by law in any development project in Sweden, the health component included is usually vague. The aim of this study was to understand the experiences and perceptions of the Sámi community regarding the current and potential health effects of the proposed mine.A qualitative study, including six in-depth interviews with members of the community, was conducted in 2020. Interviews were analysed using thematic analysis. Five themes were identified and organised in current and future impacts. Current impacts included "It's like David's battle against Goliath", "It's a slow process that takes a lot of power and energy", "It's a defense … like, to protect oneself"; with future impacts including: "If the reindeer die, everything dies", "You would feel that you do not possess any power, [you would feel] overridden, pushed away, not liked".The fear of losing current and future generations' livelihoods appeared to be the main mediators of the current and potential worsened mental health experienced by the community.